DIGITAL COMMUNICATION STRATEGY FOR OPTIMIZING MEDIAPRENEURIAL NETWORKS ON THE REALITASONLINE.ID ONLINE MEDIA PLATFORM - Fathurrahman Fathurrahman; Anang Anas Azhar (Journal Analytica Islamica, 2026)
This study aims to analyze the formulation and implementation of Realitasonline.id’s digital communication strategy in Medan, as well as the supporting and inhibiting factors affecting its efforts to optimize mediapreneurial networks. Employing a descriptive qualitative approach with a single-case study design conducted from June to July 2026, data were collected through in-depth interviews, observation, and documentation and analyzed using the Miles and Huberman interactive model. The findings indicate that the strategy formulation has shifted toward a data-driven approach by utilizing Google Analytics and a content management system (CMS) to produce hyperlocal content and popular thematic coverage, with a monthly production target of 1,500–2,000 articles. At the implementation stage, the media organization applies the principles of a lean digital newsroom by streamlining coordination among contributors certified through the Journalist Competency Test (UKW), managing community engagement through WhatsApp and Facebook groups, and diversifying business revenue streams. Network optimization is supported by Amazon Web Services cloud infrastructure operated through Promedia and an internship management system. However, its implementation is constrained by staff members performing multiple roles, intense competition over publication speed, and fluctuations in audience trends. The study concludes that integrating a data-driven digital communication strategy with a lean newsroom structure is crucial to ensuring business sustainability and strengthening the cohesion of the operational network of regional online media.